Ar prūsų kalboje egzistavo lie. tekė́ti, tẽka veiksmažodžių tipas? - Jakulis, Erdvilas (Baltistica, 2001)
WERE THERE IN THE OLD PRUSSIAN LANGUAGE ANY VERBS ANALOGOUS TO LITH. tekė́ti, tẽka VERBAL TYPE? The article seeks to determine whether the Old Prussian language could have had verbs analogous to the Lithuanian type ending in -ėti in the infinitive, -a in the present tense and -ėjo in the past tense. Vytautas Mažiulis’ Prussian Etymological Dictionary directly attributes only one reconstructed verb to this type, *skelētvei, *skela ‘to owe, to be at fault’, and indirectly connects several suffixal verb forms, *peldētvei ‘to earn; to obtain’, *kabētvei ‘to hang’, *bīlet ‘to tell’ and *kalsēt ‘to ring’. The OPr. verbs under discussion, however, belong to another verbal type (with variable suffix) - inf. -ī-, praes./praet. -ā-/-ē-. The tekė́ti, tẽka verbal type arose from the past tense stem, *-ē, of root verbs with the addition of thematic personal endings, i.e., a secondary stem *-i̯ā (*tekēi̯ā). The past tense stem *-ēi̯ā suffix *-ē was then introduced into the infinitive (*tekti > *tek-ē-ti). The Prussian language added plural personal endings to vowel suffixes athematically (directly after the suffix vowel), and because the first, second and third person singular usually had a zero ending – the final vowel was that of the suffix (see Kaukienė 2000b, 58 f.). Therefore there was no basis for tekė́ti, tẽka verbs to arise. Hence we may conclude that tekė́ti, tẽka verbal type is an East Baltic innovation.